Pulse Density Modulation Flyback Converter for LED Automotive Lighting - Shinde Rohit; Ramachandiran Gunabalan; Mehtra Pavan Kumar (Institute of Advanced Engineering and Science, 2017)
Switched mode power supply (SMPS) converter is a dc-dc power electronic converter which is used to step up or step down the dc output voltage. A dimmable driver circuit for Light Emitting Diode (LED) lamp for automotive lighting with dimming feature is used in this paper. A flyback converter is used as a driver circuit operated in discontinuous conduction mode to perform dimming control of LEDs. High overall circuit efficiency is achieved by regulating the current through the LED lamps using pulse density modulation scheme. The LED driver circuit design and operating principle is discussed in detail. A gentle current control feature is achieved by pulse density modulation technique. The high performance driver circuit is designed for 25 W LED lamps.